Effect of autologous platelet rich plasma on recovery after tonsillectomy in adult patients: a randomized controlled study - Muskaan, Syeda; V., Chaitanya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Tonsillectomy is performed more frequently in children than in adults but post-operative pain is more in adults and restricts food and water intake affecting daily activities and quality of life. Healing of fossa takes 14-21 days to complete resulting in morbidity till fossa is healed. Platelet rich plasma (PRP) is known for its healing and analgesic effects and has led to its application in various conditions. This arose curiosity regarding the efficacy of PRP in healing of mucosal wound, reducing pain after tonsillectomy in adults. Methods: Patients above 18 years presenting with signs and symptoms of chronic tonsillitis were chosen. These patients underwent Tonsillectomy followed by topical application of PRP in a randomly selected test fossa. Patients were followed up for assessment of pain and healing of the tonsillar fossa till post-operative day 10 and the results were compared between test and control fossa in each patient. Results: On post-operative day 10, no patient complained of moderate pain in the test side while there was moderate pain in 4 fossae in the control side limiting their daily activities, majority of test tonsillar fossae were in stage 4 and 5 of healing; whereas control fossae were still in stage 3. Further, the onset of healing of test fossae was quite early compared to control. Conclusions: Autologous PRP being easily available and cost-effective procedure can be included in routine tonsillectomy procedure as a method to alleviate pain and promote early and accelerated healing of tonsillar fossa in adults.